Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1242/jcs.01021
|View full text |Cite
|
Sign up to set email alerts
|

αB-Crystallin-coated MAP microtubule resists nocodazole and calcium-induced disassembly

Abstract: contained αB-crystallin. Electron micrographs clearly showed direct interactions of purified αB-crystallin with the surface of microtubule-associated proteins (MAPs) attached to MTs. Purified αB-crystallin bound to MAPMTs in a concentration-dependent manner. However, αB-crystallin did not bind MTs reconstituted from purified tubulin. Finally, we observed that αB-crystallin increased the resistance of MTs to depolymerization in cells and in vitro. Taken together, these results suggest that one of the functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 54 publications
6
82
0
4
Order By: Relevance
“…Chaperone proteins possess the ability to prevent target protein interactions and aggregation of misfolded proteins 14 ; they are, thereby, protective molecules during times of stress or shock. The domain of α-B-crystallin inhibits the aggregation of tubulin and other microtubuleassociated proteins in particular [15][16][17] . Decreased α-B-crystallin occurs with muscular atrophy and is associated with decreased amounts of tubulin 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Chaperone proteins possess the ability to prevent target protein interactions and aggregation of misfolded proteins 14 ; they are, thereby, protective molecules during times of stress or shock. The domain of α-B-crystallin inhibits the aggregation of tubulin and other microtubuleassociated proteins in particular [15][16][17] . Decreased α-B-crystallin occurs with muscular atrophy and is associated with decreased amounts of tubulin 18 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, ␣-crystallin modulates the assembly of intermediate filament vimentin and stabilizes actin filaments in a phosphorylation-dependent manner (Nicholl and Quinlan 1994;Wang and Spector 1996). We reported that ␣B-crystallin associates with tubulin (Arai and Atomi 1997;Fujita et al 2004;Sakurai et al 2005). Previously, we reported that heat-induced denatured tubulin dimer aggregation could be suppressed by ␣B-crystallin, showing that ␣B-crystallin may bind to denatured/denatured intermediate forms of tubulins, but not to native tubulin dimers (Arai and Atomi 1997).…”
Section: Introductionmentioning
confidence: 98%
“…Previously, we reported that heat-induced denatured tubulin dimer aggregation could be suppressed by ␣B-crystallin, showing that ␣B-crystallin may bind to denatured/denatured intermediate forms of tubulins, but not to native tubulin dimers (Arai and Atomi 1997). In addition, ␣B-crystallin directly associates with the surface of microtubule-associated protein (MAP) microtubules (Fujita et al 2004). Denatured tubulin is reported to inhibit the assembly of native tubulin (Maccioni 1983).…”
Section: Introductionmentioning
confidence: 99%
“…After incubation with secondary antibodies, the membrane was incubated with an enhanced chemiluminescence kit (Amersham Biosciences Co., Buckinghamshire, UK). αB-crystallin was expressed in Escherichia coli (35) and purified by protein chromatography, and tubulin (phosphocellulose column purified tubulin) was purified from the porcine brain (13). The purified proteins (αB-crystallin, 5, 10, 20, 30, and 40 ng; α-tubulin, 1, 3, 5, 7, 9, and 11 ng) were used as standards for each protein because the relationship between the gradual contents of each purified protein and the linearity of band intensity is proportional.…”
Section: Sds Polyacrylamide Gel Electrophoresis (Page) and Western Blmentioning
confidence: 99%
“…Microtubules, which consist of tubulin, are associated with different fibril types depending on muscle fibers and their protein contents, and their plasticity is controlled by electrical activity (29). We previously traced these proteins to determine whether the system formed by αB-crystallin and its substrate (tubulin) responds to mechanical environmental demands resulting in morphological and biochemical responses, which lead to adaptive transformation of the skeletal muscle (13,15).…”
Section: Introductionmentioning
confidence: 99%